Separation of tocol-derivatives by elevated temperature normal-phase liquid chromatography - Sanagi, Mohd Marsin; See, Hong Heng; Wan Ibrahim, Wan Aini; Abu Naim, Ahmedy (Penerbit UTM Press, 2006)
A novel method for the separation of eight vitamin E isomers (ïƒ¡-, ïƒ¢-, ïƒ£-, ïƒ¤-tocopherol, and ïƒ¡-, ïƒ¢-, ïƒ£-, ïƒ¤ tocotrienol) and ïƒ¡-tocopherol acetate on normal phase high performance liquid chromatography (NP-HPLC) at elevated column temperature has been developed. The separation was optimized by varying the eluent composition and column temperature. All the isomers were successfully separated using NP-HPLC on amino and silica columns. By simply increasing the temperature for silica column, excellent separation efficiencies and shorter analysis times were achieved without significant loss in resolution. The developed separation method is rapid, shows excellent reproducibility, and suitable to be used as a quantitative method in analyzing tocopherols and tocotrienols.